2014
DOI: 10.1017/s0021859614000471
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil tillage system on the nitrogen uptake, grain yield and nitrogen use efficiency of spring barley in a cool Atlantic climate

Abstract: SUMMARYField experiments were conducted between 2009 and 2011 in Ireland to compare the effects of soil tillage systems on the grain yield, nitrogen use efficiency (NUE) and nitrogen (N) uptake patterns of spring barley (Hordeum vulgare) in a cool Atlantic climate. The four tillage treatments comprised conventional tillage in spring (CT), reduced tillage in autumn (RT A), reduced tillage in spring (RT S) and reduced tillage in autumn and spring (RT A+S). Each tillage system was evaluated with five levels of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…In addition, Alvarez and Steinbach (2009) reported that the effect of tillage on yield parameters depends on the crop. In a cool Atlantic climate, the variability of winter wheat grain yield under different tillage system was dependent on the rainfall and temperature of the year (Brennan et al, 2014). Minerals in plants play a major role for the maintenance of certain physicochemical processes, which are essential to life.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Alvarez and Steinbach (2009) reported that the effect of tillage on yield parameters depends on the crop. In a cool Atlantic climate, the variability of winter wheat grain yield under different tillage system was dependent on the rainfall and temperature of the year (Brennan et al, 2014). Minerals in plants play a major role for the maintenance of certain physicochemical processes, which are essential to life.…”
Section: 1mentioning
confidence: 99%
“…The effects on grain yield have ranged from an increase, a decrease or no change (Hao et al, 2001). This effect depends on weather conditions and crop sequence used, rainfall during crop establishment and on the interaction between many others parameters (Brennan et al, 2014;Ercoli et al, 2017). Furthermore, no tillage is recognized to improve soil physico-chemical properties, soil moisture, soil organic matter and biological processes (Ben-Hammouda et al, 2005;Alvarez and Steinbach, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen concentration (g kg -1 ) in daughter corms (plus corm tunics) and aerial part was measured based on Kjeldal method (AOAC, 2000). On the basis of dry stigma and daughter corms yields, nitrogen acquisition efficiency (NAE) and nitrogen use efficiency (NUE) were calculated using the following equations (Brennan et al, 2014;Koocheki and Seyyedi, 2015): NAE (%) = (Nt / Na) × 100 NUES (g g -1 ) = SY / Na NUEC (g g -1 ) = CY / Na Where: Nt is g N in the total plant m -2 , Na is g N applied m -2 , SY is g dry stigma yield m -2 , and CY is g daughter corms yield m -2 .…”
Section: Determination Of Nae and Nuementioning
confidence: 99%
“…Most of the world surface under conservation tillage (95 x 10 6 ha) is concentrated in North (47%) and South America (39%), followed at distance by Australia (9%) and with less than 0.05% in Europe, where there is still much scepticism about the suitability of conservation agriculture for the European climate conditions and cropping systems (Brennan et al, 2015;Brennan et al, 2014;Stagnari et al, 2010;Van Den Bossche et al, 2009). In the Spanish temperate humid zone, the most common rotation under conservation tillage is the maize-Italian ryegrass due to the economic and timeliness advantages without detrimental effect on yields (Bueno et al, 2007), as also reported for other Atlantic climates (Hansen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%